Relationship between physical activity and BMI with level of motor coordination performance in schoolchildren - Carla Menêses Hardman; Rildo de Souza Wanderley Júnior; Elusa Santina Antunes de Oliveira; Mauro Virgílio Gomes de Barros (Universidade Federal de Santa Catarina, 2017)
International studies have shown that motor coordination was inversely associated with adiposity, and directly associated with other health outcomes. However, there are few national studies addressing this issue and the results are divergent. The aim of this study was to analyse the relationship between physical activity and body mass index (BMI) with the level of motor coordination performance in children. This cross-sectional study was performed with children aged 5-7 years old. The level of motor performance was evaluated by normative data of the motor quotients assessed by KTK test. BMI was calculated by body weight and height. The level of physical activity was assessed by a questionnaire applied by interviewers with parents. Statistical analysis was performed by Spearman and Pearson test, and multiple linear regression. The sample included 665 children with mean age of 6.29 (± 0.75) years old, and 52.6% were male. It was verified which total motor quotient (TMQ) was directly related to physical activity score (0.096; p = 0.013) and inversely related to BMI (-0.284; p<0.001). The relationship between BMI and TMQ was moderated by family income. BMI was inversely related to the level of motor performance, and the score of physical activity was directly related to the level of motor performance in children in a higher family income.